Clinical outcome of Lenvatinib Versus Sorafenib in the Management of Advanced Hepatocellular Carcinoma: a Comparative study in Dhaka, Bangladesh - Hossain, Mohammad Shawkat; Karim, Md Fazal; Islam, Mohammad Nasirul; Podder, Provat Kumar (Sir Salimullah Medical College Journal, 2025)
Background: Hepatocellular carcinoma, the 2nd leading cause of cancer death, is a global threat around the world due to its high incidence rate. If we analyzed the last 5 to 8 years of clinical studies of different countries, the incidence of hepatocellular carcinoma (HCC) is increasing at an alarming rate. Clinical parameters play an important role in early diagnosis and overall prognosis of hepatocellular carcinoma. This study aims to assess and compare the outcome of clinical parameters of Lenvatinib versus sorafenib for the management of hepatitis B virus-related hepatocellular carcinoma. Methods: This comparative study was conducted in the department of Hepatology, Sir Salimullah Medical College Mitford Hospital, from March 2022 to September 2022, from the date of randomization to the next 6 months or till death, whichever one was earlier. A total of 24 patients diagnosed as having advanced hepatocellular carcinoma by imaging, inclusion, and exclusion criteria were enrolled by randomization and divided into two arms. Results: The majority of the patients were from the 51-60 years of age group. 28% of respondents had no exposure to schooling or were illiterate. According to BCLC staging, 16.6% of patients were at stage B. On the other hand, 45.8% of patients were in Stage A according to the Child-Pugh score using lenvatinib. Aspartate aminotransferase (AST) level is reduced compared with baseline to 3 months. Moreover, sorafenib reduced alanine transaminase (ALP) from 214.9 U/L to 98.3 U/L within 3 months. More clinical studies should be expected to be done in the future for better outcomes. Conclusion: Lenvatinib positively changes the clinical outcome in HCC patients, especially in tumor size reduction. Sir Salimullah Med Coll J 2024; 32: 59-64